2014
DOI: 10.1007/s00421-014-2990-y
|View full text |Cite
|
Sign up to set email alerts
|

Agonist and antagonist muscle activation in elite athletes: influence of age

Abstract: IANT-BF is partially related to the age of the group and to joint protection upon impact. Moreover, given the very brief duration of the task, a feed-forward mechanism modulating antagonist activation partly based on the stress imposed on the knee joint could be hypothesized. This mechanism potentially involves skill dependent re-modelling of the peripheral and central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
(77 reference statements)
1
32
0
Order By: Relevance
“…However, these inclusion criteria have been adopted to limit the variability in our experimental group, since different hormonal levels may influence sEMG characteristics (Felici et al., ). In addition, the choice of including only sedentary volunteers allowed us to increase the possibility to generalize our results, since sportsmen may present peculiar adaptations of their muscular (Quinzi, Camomilla, Felici, Di Mario, & Sbriccoli, ) and nervous systems (Berchicci, Quinzi, Dainese, & Di Russo, ) that can alter their neuromuscular activation. One last consideration should be addressed on the adoption of such devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, these inclusion criteria have been adopted to limit the variability in our experimental group, since different hormonal levels may influence sEMG characteristics (Felici et al., ). In addition, the choice of including only sedentary volunteers allowed us to increase the possibility to generalize our results, since sportsmen may present peculiar adaptations of their muscular (Quinzi, Camomilla, Felici, Di Mario, & Sbriccoli, ) and nervous systems (Berchicci, Quinzi, Dainese, & Di Russo, ) that can alter their neuromuscular activation. One last consideration should be addressed on the adoption of such devices.…”
Section: Discussionmentioning
confidence: 99%
“…Karate elite athletes are usually prescribed a mixed training regime that elicits adaptations in both anaerobic and aerobic energy pathways (6,17,44). Indeed, karate training has been shown to increase muscular strength; functional mobility; mental, moral, and physical health; and self-actualization (8,40). Moreover, recently, it has been found that intensive karate training induced higher muscle activation during the execution of karate-specific kicks (23).…”
Section: Introductionmentioning
confidence: 99%
“…In kicks, the angular momentum of the leg segment and joints are determined by the angular velocities of these segments (Quinzi et al, 2014(Quinzi et al, , 2015Sørensen et al, 1996). Furthermore, the interaction of agonist and antagonist muscle recruitment is an important determinant of the angular velocity (Sørensen et al, 1996;Sbriccoli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the interaction of agonist and antagonist muscle recruitment is an important determinant of the angular velocity (Sørensen et al, 1996;Sbriccoli et al, 2010). This interaction is traditionally visualized through the cocontraction index (Quinzi et al, 2013(Quinzi et al, , 2015. A greater cocontraction implies a higher antagonist muscle opposition to the intended movement.…”
Section: Introductionmentioning
confidence: 99%